Sistem Mitigasi Dan Adaptasi Bencana Dalam Menghadapi Potensi Acaman Mentawai Megathrust Sebagai Inovasi Teknologi Edukasi Kebencanaan - Anggraini, Putri; Boy, Wendi; Sularno, Sularno (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
The urgency of this research is to provide an understanding and education system for disaster adaptation mitigation to communities living on the coast of West Sumatra and outside West Sumatra so that people are smarter and ready to face situations that occur when a disaster strikes. In this way the risk of greater loss of life can be avoided. The aim of this research is to produce a geographic educational information system for disaster adaptation mitigation in dealing with the potential threat of the Mentawai Megathrust based on WebGIS. The method used is four-D, namely Define, Design, Development, and Disseminate. The process of presenting the model is carried out through the define stage, namely finding data about predicted locations and impacts of disasters. The second stage of design is creating a geographic mitigation and disaster adaptation educational information system application design which contains evacuation route map designs, shelter location map designs and independent evacuation animations. The third stage of development is developing the system after testing and implementing the system, the disseminate stage is socializing the use of the application to people living on the coast of West Sumatra and disseminating research results through research results books.